Gafchromic HD-V2 investigations using MeV ion beams in vacuum. Issue 11 (2nd December 2019) - Torrisi, L.; Havranek, V.; Cutroneo, M.; Torrisi, A.
ABSTRACT: Gafchromic HD-V2 films are employed to study the response to light ions useful in radiotherapy, such as protons, helium and carbon beams. The effects induced by the ions at an energy within about 300 keV and 16 MeV were investigated in terms of optical absorbance measurements in the irradiated active region of the film. The employed ion doses range between 0.4 Gy and 12 kGy. The results show that the net optical density increases almost exponentially with the absorbed dose and that it becomes saturated after prolonged dose higher than 1 kGy. The optical density produced in the film was measured by light transmission measurements at 700 nm wavelength, at which is observed the highest gafchromic sensitivity. Calibration curves of optical density versus exposure dose and type of ion are given. The dependence on the ion stopping power was presented and discussed.